Barthelonids represent a deep-branching metamonad clade with mitochondrion-related organelles predicted to generate no ATP. Issue 1934 (9th September 2020) - Yazaki, Euki; Kume, Keitaro; Shiratori, Takashi; Eglit, Yana; Tanifuji, Goro; Harada, Ryo; Simpson, Alastair G. B.; Ishida, Ken-ichiro; Hashimoto, Tetsuo; Inagaki, Yuji
Abstract : We here report the phylogenetic position of barthelonids, small anaerobic flagellates previously examined using light microscopy alone. Barthelona spp. were isolated from geographically distinct regions and we established five laboratory strains. Transcriptomic data generated from one Barthelona strain (PAP020) were used for large-scale, multi-gene phylogenetic (phylogenomic) analyses. Our analyses robustly placed strain PAP020 at the base of the Fornicata clade, indicating that barthelonids represent a deep-branching metamonad clade. Considering the anaerobic/microaerophilic nature of barthelonids and preliminary electron microscopy observations on strain PAP020, we suspected that barthelonids possess functionally and structurally reduced mitochondria (i.e. mitochondrion-related organelles or MROs). The metabolic pathways localized in the MRO of strain PAP020 were predicted based on its transcriptomic data and compared with those in the MROs of fornicates. We here propose that strain PAP020 is incapable of generating ATP in the MRO, as no mitochondrial/MRO enzymes involved in substrate-level phosphorylation were detected. Instead, we detected a putative cytosolic ATP-generating enzyme (acetyl-CoA synthetase), suggesting that strain PAP020 depends on ATP generated in the cytosol. We propose two separate losses of substrate-level phosphorylation from the MRO in the clade containing barthelonids and (other) fornicates.